Toppling Induced Movements In Large, Relatively Flat Rock Slopes - Adrian Brown (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1982)
Over the last decade, a number of large slopes have been excavated in rock which contains families of joints or faults which dip steeply into the cut slope. Despite the absence of "adverse" structures, these slopes have exhibited alarming movement rates at very modest heights (as little as 100 meters) and slope angles (as little as 20º). Classical stability analysis suggests that such slopes should be unconditionally stable. This paper describes the toppling mechanism which has been found to be the cause of the observed movements and develops a general method for analysis of it. Simple cases are analyzed in order to provide charts which allow quick evaluation of the likelihood of this phenomenon occurring. The safety implications of such movements in slopes are also examined.